Synergy of Islamic Economics and SDGs: Strategy Toward Golden Indonesia 2045 Inclusion in Indonesia - As'ari, Muhammad; Huda, Nurul (CV. Civiliza Publishing, 2025)
The transformation of the global economy demands financial systems and development policies that are inclusive, sustainable, and equitable. Islamic economics, through instruments such as Islamic banks, zakat, waqf, takāful insurance, and sukuk, holds significant potential to support the achievement of the Sustainable Development Goals (SDGs) in Indonesia. This article examines the synergy between Islamic economic principles and SDG targets, identifies key instruments (productive zakat, green sukuk, Islamic financial inclusion), and formulates policy strategies to accelerate the contribution of the Islamic sector toward the “Golden Indonesia 2045” vision. The findings show that (1) Islamic financial instruments have demonstrated initiatives toward SDG integration but still require stronger impact measurement and transparent governance; (2) zakat and waqf can be positioned as social development instruments targeting poverty and inequality (SDG 1 & 10); and (3) green sukuk and Islamic green finance products offer sustainable infrastructure financing pathways. Recommendations include regulatory harmonization, capacity building for zakat/waqf management institutions, SDG-based reporting standards, and fiscal incentives for Islamic green instruments.